Highly Selective Directional Atomic Layer Etching of Silicon. (4th March 2015) - Tan, Samantha; Yang, Wenbing; Kanarik, Keren J.; Lill, Thorsten; Vahedi, Vahid; Marks, Jeff; Gottscho, Richard A.
Abstract : Following Moore's Law, feature dimensions will soon reach dimensions on an atomic scale. For the most advanced structures, conventional plasma etch processes are unable to meet the requirement of atomic scale fidelity. The breakthrough that is needed can be found in atomic layer etching or ALE, where greater control can be achieved by separating out the reaction steps. In this paper, we study selective, directional ALE of silicon using plasma assisted chlorine adsorption, specifically selectivities to bulk silicon oxide as well as thin gate oxide. Possible selectivity mechanisms will be discussed.